Microstructure of the relaxed (001) Si surface - Kiv, A.E.; Soloviev, V.N.; Maximova, T.I. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2000)
MD computer simulation with the Stillinger-Weber potential have been performed to study a microstructure of silicon surface layers and relaxation processes induced by low energy ion beams. New peculiarities of relaxed (001) silicon surface were discovered by using the improved calculation scheme for diamond-like structure simulation. It was established that the relaxed microstructure of clean (001) Si surface is characterized by dangling bonds in the first three near-surface layers and by non-hexagonal polygons. Besides, the dimer formation was observed not only in the first layer. New space configurations of dimers were found. Ascertained were some conditions which lead to the effect of radiation-stimulated relaxation of surface layers under the ion bombardment in the energy region of the threshold of elastic atomic displacements in silicon.